Preparation and photocatalytic activity of mesoporous CeO2-TiO2 mixed oxides - Yan, Huijun; Gao, Hong; Li, Xuanyi; Hu, Hongjie (Frontiers in Materials, 2025)
In this paper, a series of mesoporous CeO2-TiO2 mixed oxides are synthesized through evaporation-induced self-assembly method. These mesoporous CeO2-TiO2 mixed oxides are characterized using XRD, FT-IR, Raman, TEM and N2 adsorption-desorption. The obtained samples exhibit a fully ordered mesoporous structure, when the template is completely removed. The research results show that the mesoporous CeO2-TiO2 mixed oxides possess a high surface area and small particle size. The effects of Ti/Ce molar ratio on the photocatalytic activity are investigated. The results indicate that mesoporous CeO2-TiO2 composite oxides with Ti:Ce = 1:0.1, after calcination at 500°C, exhibit the highest photocatalytic activity.